The effectiveness of M-learning over traditional method among the medical students - Mithrason, Arun T.; Thomas, Vijatha (International Journal Of Community Medicine And Public Health, 2019)
Background: We are living in an era of technology where smart phones and hence social media have entered into many aspects of our life. Social media tools are gaining attention in medical education as well. Therefore, this study was done to find out the effect of M-learning via WhatsApp over the traditional method and also to know the students’ perception towards M-learning via WhatsApp. Methods: The study included 60 sixth semester students and they were divided into two groups of 30 each. 4 sessions were conducted on nutrition and occupational health. For the first 2 sessions, group I was intervention group (TL method was WhatsApp) and group II was control group (TL method was lecture). For the next 2 sessions, group II was interventional group (TL method was WhatsApp) and group I was control group (TL method was lecture). To assess the effectiveness of WhatsApp intervention, a test was conducted using 60 MCQs. To evaluate the participant’s perception towards M-learning via WhatsApp, a feedback questionnaire was used. Data was analyzed using SPSS 20. Results: There was a statistically significant difference between the 2 groups of students. Interventional-group perceived WhatsApp sessions to be effective than traditional lecture. Conclusions: In our study we found a significant difference between gains of knowledge from WhatsApp compared to didactic lectures. Students were favourably inclined to use the WhatsApp and welcome its role in enhancing their learning experience.